2017
DOI: 10.1590/1678-457x.29816
|View full text |Cite
|
Sign up to set email alerts
|

Pereskia aculeata: biological analysis on wistar rats

Abstract: Pereskia aculeata Mill., a species of the family Cactaceous, popularly known in Brazil as ora-pro-nobis, has high protein, vitamin and mineral contents. High essential amino acid concentrations should be underscored, suggesting a better evaluation of the fractions. Current study quantifies amino acid content and the chemical score (CS) of protein amino acids, determining in vivo digestibility, protein efficiency ratio (PER) and net protein ratio (NPR) of P. aculeata. Plant material was collected, washed, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
3
1
5
Order By: Relevance
“…The average body weight showed no statistical difference between groups (Figure 2), differing from other studies with Wistar rats (20,21) , in which the cacti reduced this physiological parameter. Rats fed a hypercaloric diet with 5 and 10% Pereskia grandifolia flour reduced body weight (3) .…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The average body weight showed no statistical difference between groups (Figure 2), differing from other studies with Wistar rats (20,21) , in which the cacti reduced this physiological parameter. Rats fed a hypercaloric diet with 5 and 10% Pereskia grandifolia flour reduced body weight (3) .…”
Section: Resultscontrasting
confidence: 84%
“…The group in which the Pereskia grandifolia juice (HPg) was administered had a lower total weight gain than the other groups of cacti (HPa and HPb) which were equal to each other and the H group. The reduction in weight gain was observed in rats that ingested Pereskia aculeata flour (20,21) .…”
Section: Resultsmentioning
confidence: 98%
“…In spite of the aforementioned studies evidencing the nutritional and ethnopharmacological relevance of ora-pro-nobis leaves, information on their phytochemical constitution remains limited. The majority of the papers that performed chemical evaluation contemplated the amino acids and phytosterol profiles, also focusing on its essential oil (Pinto & Scio, 2014;Pinto, Machado, et al, 2015;Souza et al, 2016;Zem, Helm, Henriques, Cabrini, & Zuffellato-Ribas, 2017). A few works have indicated that phenolic compounds and carotenoids are the major antioxidant constituents of P. aculeata leaves (Agostini-Costa, Wondraceck, Rocha, & Silva, 2012;Pinto et al, 2012;Pinto, Duque, et al, 2015), however, to our best knowledge, an advanced characterization of its phenolic constitution is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al (2008) developed a pasta containing 1.0, 1.5 and 2.0 % of orapro-nobis flour, increasing the protein, fibre and mineral contents when compared the product with the control pasta. Zem et al (2017) produced flour of P. aculeata and investigated its effects on a diet applied in rats. They concluded that it might not be adequate to warrant satisfactory growth levels of the animals when provided in the diet a single protein source (P. aculeate flour).…”
Section: Nutraceutical and Food Applicationmentioning
confidence: 99%